2015
DOI: 10.1093/jamia/ocv058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tablet computers with a mobile patient portal application on hospitalized patients’ knowledge and activation

Abstract: Additional research is needed to identify optimal methods to engage and inform patients during their hospitalization, which will improve preparation for self- management after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 36 publications
4
84
0
1
Order By: Relevance
“…Our results build on the Schmaderer study by demonstrating the importance of admission type in predicting low patient activation. These results are important for other researchers who are using the PAM-13 to measure patient activation in inpatient randomized controlled trials [8,17]. …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results build on the Schmaderer study by demonstrating the importance of admission type in predicting low patient activation. These results are important for other researchers who are using the PAM-13 to measure patient activation in inpatient randomized controlled trials [8,17]. …”
Section: Discussionmentioning
confidence: 96%
“…Validating the PAM-13 in the inpatient setting is important as there are over 35 million hospital admissions each year [16] and interventions to impact patient engagement in the hospital are becoming more commonplace [8,1719]. The purposes of this paper are 1) to describe the psychometric properties (internal consistency reliability and construct validity) of the PAM-13 for hospitalized cardiology and oncology patients with planned and unplanned admissions; and 2) conduct an exploratory analysis to examine the predictors of low activation in the same population.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals can use iPET for distraction and anxiety reduction, patient education, and augmenting/enhancing several aspects of clinical nursing practice [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Veteran’s Administration has tested a paper-based daily plan for patients in the inpatient setting and found that among patients who responded to the survey, the majority found it increased their understanding of their treatment, and improved care and satisfaction [62]. O’Leary and colleagues [63] have also conducted a study showing that the provision of a mobile patient portal application to hospitalized patients was able to increase the patients’ knowledge of physician names and roles. This study had an intervention group that received an inpatient portal including information about the care team, medications, and plan for the day.…”
Section: Discussionmentioning
confidence: 99%